Proximity of Women Representations: Male Writers' Panorama in Selected Prose Fiction - Johniel Acala Seño; Matilda H Dimaano (Universitas Sanata Dharma, 2025)
This study explores how male writers portray women in prose fiction and how these portrayals reflect or differ from real-life gendered experiences across historical periods. The study aimed to (1) analyze the differences in the portrayal of Filipino women’s representation in terms of morals and decision-making in different periods and (2) investigate how prose fiction written by Filipino male authors reveals the proximity of women’s representation to real-life gender experiences. A descriptive-qualitative research design was employed, using content analysis and narrative analysis to examine five selected prose fictions from the Pre-Colonial Period (900-1565), Spanish Period (1565-1898), Early 20th Century Period (1901-1950), 20th Century Period (1951-2000), and for 21st Century or Contemporary Period (2001-Present). Feminist literary criticism guided the interpretation of each text. Significant findings reveal that Filipino women’s morals and decision making in precolonial and late 20th century periods were largely conformed to social norms, whereas Spanish, early 20th, and 21st century periods were often exhibited moral deviance and assertive decision making. The findings revealed that women were represented in distinct roles that evolved through time, from cultural leaders and nurturers to silent sufferers and survivors. While some female characters conformed to social norms, others defied them, showing inner strength and resistance. These representations reflect actual challenges faced by women, such as limited power, emotional labor, and objectification. In conclusion, the selected male-authored prose fiction closely mirrors gendered realities and highlights the gradual shift toward recognizing women’s strength and evolving roles in society.